Health Literacy and Knowledge of Cardiovascular Risk Factors in Middle-Aged Adults: Associations with Sociodemographic and Clinical Characteristics - Reyhan Kaygusuz Benli; Emel Mete; Özden Yaşarer; Berivan Beril Kılıç (Acıbadem Üniversitesi Sağlık Bilimleri Dergisi, 2026)
Purpose: Health literacy is the ability to access, appraise, and apply health information is a key determinant of preventive behaviours and health outcomes. As cardiovascular disease (CVD) remains the leading cause of death worldwide, evaluating health literacy and knowledge of cardiovascular risk factors in middle-aged adults is essential for developing effective prevention strategies. This study aimed to examine knowledge of cardiovascular risk factors and health literacy according to sociodemographic and clinical variables and to explore the association between knowledge of cardiovascular risk factors and health literacy.Methods: This cross-sectional study included 84 adults aged 45–60 years (mean age 52.79 ± 5.79). Data was collected via an online form. knowledge of cardiovascular risk factors was measured by using the Cardiovascular Risk Factors Knowledge Level Scale (CARRF-KL), and health literacy was assessed using the Turkish Health Literacy Scale-32 (THLS-32).Physical activity level, sociodemographic characteristics (age, sex, education, income, marital status) and clinical factors (hypertension, diabetes, hypercholesterolemia, smoking, obesity) were recorded. Group comparisons were performed using nonparametric tests, and associations between variables were assessed Spearman’s correlation analysis.Results: 51.2% of the participants were female. Overall, 62% had inadequate or limited health literacy, and only 13% had excellent literacy. CARRF-KL scores were significantly higher among females, non-smokers, those with hypercholesterolemia, and less active participants (p